Training specialists in international relations: rethinking the new paradigm - E. V. Voevoda (Vestnik MGIMO-Universiteta)
The article considers new tasks of universities and faculties training students of international relations. The author analyzes the essence of the concept "paradigm" in education because paradigm serves as the basis of the educational process in universities. The content of professional education depends on the aims of professional education of specialists in international relations. The process of globalization, global changes, challenges and threats bring about the necessity to study specific features of international cooperation in ecology, psychology of conflict, psychology of leadership, etc. In the age of globalization, national economies are converging while national cultures are diverging. Representatives of different nations realize the importance of preserving cultural identity. It is of vital importance to instil tolerance in future specialists in international relations and prepare them for cross-cultural communication. At the same time, it is necessary that they should not only enjoy individual freedom and national cultural identity, but realize their own responsibility to the state. In the modern world, the axiological and educational functions of professional training are growing. At the same time, it is crucial to let the students build a number of professionally relevant competences that will make it possible for them to effectively perform their professional functions. It is the competence-based approach that makes the basis of Federal state education standards, including education standards for faculties of international relations. Another direction that needs developing is training and retraining lecturers for universities specializing in international relations. Foreign language training of lecturers in basic subjects will make it possible for the, to give lectures in foreign languages, particularly in English, which, in its turn, will help to make Russia's universities more competitive.